Readings in Islamic da'wah - Hussain, Mohd. Yusof (IIUM Press, 2009)
This book contains a collection of twenty essays on a wide range of topics ranging from theory, principles and practices of Islamic da'wah to a wide spectrum of audience which include leaders, women, youth, children, prisoners Christians, Jews and Buddhists. The comprehensiveness of the topics covered which include topics never published before make the book unique and must be read by students and practitioners of Islamic da'wah in Malaysia and other parts of the Muslim world.